2012
DOI: 10.5090/kjtcs.2012.45.6.396
|View full text |Cite
|
Sign up to set email alerts
|

Brace Compression for Treatment of Pectus Carinatum

Abstract: BackgroundSurgery has been the classical treatment of pectus carinatum (PC), though compressive orthotic braces have shown successful results in recent years. We propose a non-operative approach using a lightweight, patient-controlled dynamic chest-bracing device.Materials and MethodsEighteen patients with PC were treated between July 2008 and June 2009. The treatment involved fitting of the brace, which was worn for at least 20 hours per day for 6 months. Their degree of satisfaction (1, no correction; 4, rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…This conservative approach gained popularity in the last two decades and is now the first-line therapy for CG type [5,6]. Considering that the major complaint of these patients is body image, brace compression has the advantages of being non-invasive and more cost-effective, and avoids an operative scar [6][7][8][9][10]. Nevertheless, brace compression can be complicated by local pain and skin erosion, and may be an obstacle for physical activity and social life [3,8,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conservative approach gained popularity in the last two decades and is now the first-line therapy for CG type [5,6]. Considering that the major complaint of these patients is body image, brace compression has the advantages of being non-invasive and more cost-effective, and avoids an operative scar [6][7][8][9][10]. Nevertheless, brace compression can be complicated by local pain and skin erosion, and may be an obstacle for physical activity and social life [3,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, brace compression can be complicated by local pain and skin erosion, and may be an obstacle for physical activity and social life [3,8,11]. Since the results of brace therapy are related to the duration of compression, compliance is critical for success [3,7,10]. It seems that patients use brace compression for less time than prescribed, which extends the correction phase [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000, there have been many reports on REVIEW the use of classic braces for the treatment of the carinatum deformity. [40][41][42][43][44][45][46][47] In 2008, Martinez-Ferro et al [6] published an 8-year review on the use of a specially designed dynamic compression system (the FMF Dynamic Compression System) ( Fig. 11).…”
Section: Non-surgical Treatmentsmentioning
confidence: 99%
“…4,17-21 A wide range of success rates has been reported with other types of braces using a variety of protocols, varying from 40 to 100%. 16,[22][23][24][25][26][27] The large number of publications on bracing PC within the past 15 years attests to the increasing use of this modality versus surgery. A recent review recommended bracing as first line treatment for PC.…”
Section: Bracingmentioning
confidence: 99%
“…Most studies of bracing have identified lack of compliance as the main cause of failure. [16][17][18][19][20][21][22][23][24][25][26][27] Two recent studies have specifically looked into the issue of compliance. 25,29 Pessanha et al found that patients were likely to be noncompliant with duration rather than frequency of brace wear, that is, they wore the brace daily, but for shorter periods than prescribed.…”
Section: Bracingmentioning
confidence: 99%